The effect of fermentation on the cyanide and protein contents of cassava (manihot esculenta Crants) roots. - Gumafelix, Ira Candice C. (2019.)
The effect of different fermentation conditions on the cyanide and protein contents of grated cassava roots was observed. The decrease in the level of cyanide after 2, 4, 6, and 8 days of fermentation was significantly different compared to that of the initial level at day 0. A significant difference on the mean cyanide content of day 2 can be observed when compared to that of day 6 and 8; and day 4 when compared to that of day 6 and 8. The cyanide reduction at day 6 and 8 was 100% indicating that both had decreased the cyanide significantly. The effect of solid-state fermentation and submerged fermentation was also not significantly different as well as the presence or absence of yeast. The increase in the protein of the grated cassava at different fermentation conditions was significantly different. The 8th day fermentation with yeast had higher amount of protein at 3.08%. It was observed that those that contained yeast had higher amount of protein in every fermentation day. The results for cyanide content suggest that solid-state and submerged fermentation with or without the presence of yeast will decrease the cyanide content of cassava without a significant difference. The result for the crude protein analysis suggests that addition of yeast during fermentation will significantly increase the amount of % crude protein in cassava.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Cassava -- Roots; Manihot esculenta Crantz